Why Optimistic Message Logging Has Not Been Used In Telecommunications Systems - Huang, Yennun; Wang, Yi-Min (Institute of Electrical and Electronics Engineers, Inc., 1995)
Much of the literature on message logging and checkpointing in the past decade has been based on a so-called optimistic approach [1] that places more emphasis on failure-free overhead than recovery efficiency. Our experience has shown that most telecommunications systems use a pessimistic approach because the main purpose of using message logging and checkpointing is to achieve fast and localized recovery, and the failure-free overhead of a pessimistic approach can often be made reasonably low by exploiting applications-specific information.